Patterns of psychological distress related to regular methamphetamine and opioid use - Darke, S.; Torok, M.; McKetin, Rebecca; Kaye, S.; Ross, J. (Informa Healthcare, 2011)
In order to determine the independent associations of methamphetamine and heroin use to global psychological distress, symptom patterns and personality disorder, 400 regular users of these drugs were administered the Brief Symptom Inventory. The mean global severity score was 2.39 standard deviations above the population norm, and 24% were classified as cases. After controlling for potential confounders, higher levels of global psychological distress were independently associated with more frequent use of both drug classes. Depression was associated with the frequency of heroin use, but not with methamphetamine use. Phobic anxiety, interpersonal sensitivity and psychoticism were independently related to the frequency of methamphetamine use, but not to heroin use. Neither methamphetamine nor heroin use were independent correlates of a diagnosis of borderline personality disorder or conduct disorder. Whilst higher levels of psychological distress were associated with both methamphetamine and heroin use, symptom patterns were differentially related to the use of these drugs. Copyright © 2011 Informa UK Ltd.